A case study: Re-evaluating the biological risk following a processing aid change on a marketed cardiovascular implant device - Hsia, Frances K.; Stornetta, Alessia; Soucy, Nicole V. (Frontiers in Medical Technology, 2022)
Per ISO 10993-1:2018, a processing change to a medical device requires re-evaluation of biological risk. Here, we present the biological evaluation of a marketed cardiovascular implant following a detergent formulation change. This change was initially assessed through a qualitative toxicological risk assessment based on the fully disclosed detergent formulation and a limited panel of biological testing. The conclusion was that the new detergent did not impact the biological safety of the device. This assessment was rejected during regulatory review, and extractables and leachables under exhaustive extraction conditions were then evaluated for devices processed with new versus original detergent. New extractables were present at low levels (2-65 µg/device), and a toxicological risk assessment concluded no concern. The regulatory agency responded requesting additional biological testing to evaluate local effects, further characterization of compounds with a “tentative” identification, and leachable data to support clinically relevant exposure estimates. All additional data was collected per the agency request. Still, the conclusion, considering all data, was unchanged, suggesting the extensive chemical characterization and repeat biological testing unnecessary, especially considering animal use. This case study highlights the recent shift in regulatory expectations around chemical characterization and questions the value of additional biological testing when faced with low extractable levels of low toxicity concern. It also demonstrates the need to hold to key portions of the ISO 10993 risk management framework to avoid excessive burden on medical device development when there is little to no determined risk to patient safety.